Sustainable development and innovation in the energy sector - Steger, Ulrich; Achterber, Wouter; Blok, Kornelis; Bode, Henning; Frenz, Walter; Gather, Corinna; Hanekamp, Gerd; Imboden, Dieter; Jahnke, Matthias; Kost, Michael; Kurz, Rudi; Nutzinger, Hans G.; et al. (Springer, 2005)
Problem definition, tasks, procedure and derivation of recommendations for action - Terminological and conceptional foundations - Normative criteria for evaluation and decision-making - Towards a sustainable energy system. Legal basis, deficits and points of reference - Potentials for the sustainable development of energy systems - The reality of sustainability: conflicts of aims in the choice of instruments - Strategies for accelerating sustainable energy innovations - On the political enforceability of a sustainable innovation strategy - Responsibility for the "Energy Hunger" of the developing countries. How sustainable energy innovations can help - Appendix.